Training in oral and maxillofacial surgery in Germany: residents’ satisfaction and future challenges - Zeller, Alexander; Thiem, Daniel G. E.; Bartella, Alexander K.; Seifert, Lukas B.; Beiglboeck, Fabian M.; Hoffmann, Jürgen; Ehrenfeld, Michael; Pabst, Andreas (Journal of cranio-maxillofacial surgery, 2021)
The aim of this study was to analyze the current situation of trainees in OMFS in a nationwide survey at German universities and teaching hospitals. A questionnaire about their training in OMFS and discrimination, gender (in-)equality, and reconcilability of work and family life was sent to many OMFS residents in Germany. Seventy-five questionnaires were included. The average age of the participants was 32.15 years (± 0.75 years); 47 participants were male, 22 female, and 3 “diverse”. The participants’ overall satisfaction rate was good. Training concepts existed in most of the teaching hospitals (54.67%). 8.11% of the participants stated discrimination existed against men while, 24.32% agreed that discrimination existed against women. Stating that discrimination against women exists, it was associated with female gender (p < 0.001), being married (p = 0.042), and not aiming for further academic degrees (p = 0.009). Overall, the training situation in Germany seems structured in most teaching hospitals. Apart from the residents’ general satisfaction with the training concepts, there seems to be a matter of concern regarding discrimination especially against women and the reconcilability of work and family life in OMFS training. Furthering the establishment of structured training concepts might be useful to overcome these issues in the course of training in OMFS.